Evolution and function of fossoriality in the Carnivora: implications for group-living - Noonan, Michael J.; Newman, Chris; Buesching, Christina D.; Macdonald, David W. (Frontiers in Ecology and Evolution, 2015)
The societies of group-living carnivores that neither hunt nor interact cooperatively may arise due to ecological drivers and/or constraints. In this study we evaluate whether group-living may be intrinsically associated with fossoriality; a link that is well supported in other taxa, but hitherto under-evaluated in the Carnivora. We make two over-arching predictions: i) that fossoriality will be associated with carnivoran sociality; and ii) that this association will be most evident in those species making extended use of subterranean dens. From a meta-analysis of key behavioural, ecological, ontological, and trophic traits, we demonstrate that three quarters of carnivore species exhibit some reliance on underground dens. Congruence between life-history traits and metrics of fossoriality evidenced that: 1) there are phylogenetic, and morphological constraints on wholly fossorial life-histories; 2) fossoriality correlated positively with the extent of offspring altriciality, linked to the use of natal dens; 3) burrow use increased with latitude; and 4) insectivorous carnivores were more fossorial than predatory carnivores. Corroborating work in the Rodentia, fossorial traits associated strongly with carnivoran group-living tendencies, where species utilising subterranean natal dens are 2.5 times more likely to form groups than those that do not. Furthermore, using comparative analyses, we evidence support for an evolutionary relationship between diet, fossoriality and sociality. We propose that fossorial dens act as a safe haven, promoting fitness benefits, territorial inheritance and cooperative breeding. We conclude that, among smaller (<15kg) den-using carnivores, and especially for omnivorous/ insectivorous species for which food resource dispersion is favorable, continued cohabitation at natal dens can promote cohabitation among adults; that is, philopatric benefits leading to (not necessarily cooperative) spatial groups.